How does Organizational Communication affect Job Satisfaction among Employees of Automotive Companies? - Fasiha; Fatma Sarie; Suharto; Andi Naila Quin Azisah Alisyahbana; Andika Isma (Fundamental and Applied Management Journal, 2023)
This research aims to find out how organizational communication influences job satisfaction among automotive company employees. The population in this study were all internal employees of companies operating in the automotive sector, or in this case PT Hadji Kalla Toyota, totaling 80 people. The instruments used in the research were observation, documentation, and questionnaires. The data analysis technique used is simple linear regression analysis and partial hypothesis testing using the IBM Statistical for Product and Service Solution (SPSS) version 21 program. Based on the results of statistical tests, it shows that partially the organizational communication variable has a positive and significant effect on employee job satisfaction. Based on the results of this research, PT Hadji Kalla Toyota should maintain and improve organizational communication by creating a work environment that is not rigid, because a rigid work environment can cause communication between employees to decrease. By establishing good communication, this variable can increase job satisfaction employee.